Answer:
x = 13
Step-by-step explanation:
Step 1: Define
f(x) = (x - 1)/2
f(x) = 6
Step 2: Substitute and solve for <em>x</em>
6 = (x - 1)/2
12 = x - 1
x = 13
Answer: 3
Step-by-step explanation:
y-3=2(x+1)
y - 3 = 2x + 2
+3. +3
y=2x+5
-1 is the x value so plug it in where the x is in the equation
y=2(-1) +5
y= -2 + 5
y= 3
Answer:
yufcyiciygciykgc, nbhgcv
Step-by-step explanation:
98yfgouyfuchkgcbvkhgcihdiytdiytditdytdiytdityghvhgcxdfsrtyuhkjbhcgfdxzsaewrsdxfhgyujkhjmnb cvngfjkhji
Answer:
Step-by-step explanation:
Answer:
What are the possible answers?